2003
DOI: 10.1152/ajpregu.00111.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial proliferation in the permanent vs. temporary cold: enzyme activities and mRNA levels in Antarctic and temperate zoarcid fish

Abstract: Adjustments in mitochondrial properties and capacities are crucial in acclimatization to seasonal cold and in evolutionary cold adaptation of marine ectotherms. Although long-term compensatory increments in aerobic capacity of fish tissues have frequently been described in response to cold, much less is known about transitional phases and gene expression patterns involved. We investigated the time course of adjustment to acute cold in liver of eurythermal eelpout Zoarces viviparus. Whereas citrate synthase (CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 38 publications
7
81
1
Order By: Relevance
“…Cold compensated CS activities after calculation for total liver were also found by Kent et al (1988) and Lannig et al (2003), though it is somewhat unexpected that the slightly lower specific enzyme (CS and IDH) activities in liver mitochondria of cold compared to warm acclimated North Sea eelpout remained uncompensated for despite the higher mitochondrial protein content in Z. viviparus acclimated to 5°C. In contrast to the present findings, Lucassen et al (2003) found higher CS activity per g liver during cold acclimation (3.5°C) in North Sea eelpout, however, it might be that cold compensation of CS activities only starts when temperature falls below 5°C. Lucassen et al found no differences in hepatosomatic indices, whereas, in the present study, cold acclimation led to elevated I H in Z. viviparus.…”
Section: Effects Of Temperature On Mitochondrial Enzymescontrasting
confidence: 99%
See 1 more Smart Citation
“…Cold compensated CS activities after calculation for total liver were also found by Kent et al (1988) and Lannig et al (2003), though it is somewhat unexpected that the slightly lower specific enzyme (CS and IDH) activities in liver mitochondria of cold compared to warm acclimated North Sea eelpout remained uncompensated for despite the higher mitochondrial protein content in Z. viviparus acclimated to 5°C. In contrast to the present findings, Lucassen et al (2003) found higher CS activity per g liver during cold acclimation (3.5°C) in North Sea eelpout, however, it might be that cold compensation of CS activities only starts when temperature falls below 5°C. Lucassen et al found no differences in hepatosomatic indices, whereas, in the present study, cold acclimation led to elevated I H in Z. viviparus.…”
Section: Effects Of Temperature On Mitochondrial Enzymescontrasting
confidence: 99%
“…Lucassen et al found no differences in hepatosomatic indices, whereas, in the present study, cold acclimation led to elevated I H in Z. viviparus. It may well be that longterm cold acclimation (10 months in this study versus 25 days in the study by Lucassen et al 2003) led to a down-regulation of specific CS capacities associated with an increase in I H .…”
Section: Effects Of Temperature On Mitochondrial Enzymesmentioning
confidence: 71%
“…Thermal adaptation is linked to temperature dependent gene expression, for example of key aerobic enzymes, as seen during seasonal as well as latitudinal cold adaptation (e.g. Hardewig et al, 1999;Lucassen et al, 2003). Rearrangements of aerobic metabolism also occur with a shift to lipid accumulation and energy storage (cf.…”
Section: Trade-offs In Thermal Adaptation Setting Functional Limitsmentioning
confidence: 99%
“…Eventually, this even led to the loss of respiratory proteins in the white blooded Channichthyidae (Di Prisco 2000). The downside of this high degree of coldspecialisation was the development of cold-stenothermy, mirrored by increased mitochondrial densities at uncompensated capacities (Johnston et al 1998;D'Amico et al 2002;Lucassen et al 2003) combined with reductions in hematocrit (Egginton 1997b) and cardiovascular output (Egginton 1997a). Specialisation has thus forced some of these species to lead a less active, rather sluggish lifestyle.…”
Section: Introductionmentioning
confidence: 99%